WORK SKILLS PROGRAM THROUGH APPRENTICESHIP PROGRAM FOR CHILDREN WITH MILD MENTAL RETARDATION - Mastiani, Emay; Suwandari, Lilis (PEOPLE: International Journal of Social Sciences, 2017)
Work skills for children with mild mental retardation are very important, since the skills will be their assets for the future.There are two benefits that will be obtained if the learning skills are acquired directly in the workplace, namely; First the children will quickly understand the work. Second, the children’s skill will directly be recognized by the employer – thus it does not require any tests for applying for the job. The research is intended to find out the learning skill work through apprentices whether to accelerate the comprehension of the child compared with learning work skill at school. The selection of skill programs is adjusted according to the work with the physical, mental / cognitive, social and conditions, and the children’s interest on the job as well as the employer‘s acceptance for the children with mild mental retardation.Some work can be done by the children with mild mental retardation, because the available work is not too difficult and does not require thinking. The available jobs tend to require hand work. The used method in this research is research and development(R& D). The data are obtained through observation, interview, documentation workshop discussion, and limited validation. The results showed that the children with mild mental retardation were able to do semi-skilled jobs, as well as the employers are willing to accept the children who want to work in the workplace. As for the recommendations the schools should try to apply work skills program through apprenticeship.